The effect of tai chi intervention on NLRP3 and its related antiviral inflammatory factors in the serum of patients with pre-diabetes - Hu, Shujuan; Hu, Yingxing; Long, Peilin; Li, Peixiong; Chen, Ping; Wang, Xianwang (Frontiers in Immunology, 2022)
Background: NLRP3 inflammasome and its related antiviral inflammatory factors have been implicated in the pathogenesis of type 2 diabetes mellitus (T2DM) and insulin resistance, but its contribution to pre-diabetes remains poorly understood. Objective: To investigate the effects and the potential mechanism of Tai Chi intervention on NLRP3 inflammasome and its related inflammatory factors in the serum of middle-aged and older people with pre-diabetes mellitus (PDM). Methods: 40 pre-diabetic subjects were divided into a pre-diabetic control group (PDM-C group, N=20) and a Tai Chi group (PDM-TC group, N=20) by random number table. 10 normoglycemic subjects (NG) were selected as controls. We measured clinical metabolic parameters and collected blood samples before and after the 12 weeks of Tai Chi intervention. Antiviral inflammatory factors in serum were detected by enzyme-linked immunosorbent assay. Results: The blood glucose, insulin resistance, and inflammation in PDM groups were higher than in the NG group (P<0.05 and P<0.01, respectively). The results also suggested that 12 weeks of Tai Chi intervention could reduce body weight, blood pressure, blood glucose, insulin resistance, blood lipid, and the expressions of serum inflammatory factors in the pre-diabetic population. Conclusion: Tai Chi intervention may improve blood glucose, lipid levels, and insulin resistance in middle-aged and elderly pre-diabetic patients by reducing the level of NLRP3 inflammasome and its related inflammatory factors.